Pengaruh Pajak Parkir Dan Pajak Restoran Terhadap Pendapatan Asli Daerah Kota Medan - Alda Amelia Siregar; Kusmilawaty Kusmilawaty (JAS (Jurnal Akuntansi Syariah), 2022)
This research aims to show the effect of parking and restaurant taxes on local revenue in the city of Medan. This research uses a quantitative method with a descriptive approach. The research population is parking tax, restaurant tax, and Medan city original income in 2015-2020. The sampling technique used the purposive sampling technique and obtained 21 samples. The data source uses secondary data in the form of documentation of parking taxes, restaurant taxes, and local revenue for the city of Medan in 2015-2020. Data analysis using multiple linear regression. The results showed that the parking tax did not affect the local revenue of Medan city. Restaurant tax positively and significantly affects local revenue in the city of Medan. Simultaneously parking and restaurant taxes significantly affect local revenue in Medan, with a significant effect of 59.4%. This research can be a reference for the Medan city government in improving strategies for collecting taxes, especially parking taxes so that Medan city's original revenue can increase.